Effects of exercise intensity on recovery of autonomic nervous system immediately after exercise and during sleep, and on subjective and objective sleep quality - Syväoja, Heidi (2010)
Syväoja, Heidi. 2010. Effects of exercise intensity on recovery of autonomic nervous system immediately after exercise and during sleep, and on subjective and objective sleep quality. Master´s thesis in Exercise Physiology. Department of Biology of Physical Activity. University of Jyväskylä, 90.